Dose volume histogram constraints in patients with soft tissue sarcomas of the extremities and the superficial trunk treated with surgery and perioperative HDR brachytherapy. (May 2022) - Gómez-Álvarez, Jorge; Martín Pastor, Santiago; Gimeno, Marta; Lamo-Espinosa, José; Ramos, Luis I.; Cambeiro, Mauricio; Tagliaferri, Luca; Kovacs, Gyoergy; Strnad, Vratislav; San-Julián, Mikel; Martinez-Monge, Rafael
Highlights: WHC can be minimized by using a more conservative CTV definition. WHC can be lessened with a technique/planning aimed to reduce hyperdose CTV2cm3 areas. In Previously Irradiated patients WHC may be mimimized considering Lifetime EQD2 Skin2cm3 doses. ORN can be reduced by using the Bone2cm3 EQD2 constraint. ND occurs more frequently in patients with large tumors receiving high treated volume doses, but no specific constraints can be recommended due to the lack of peripheral nerve definition during brachytherapy planning. Abstract: Background: Wound healing complications (WHC), osteoradionecrosis (ORN), and nerve damage (ND) are common adverse effects in adult patients with soft tissue sarcomas of the extremities and the superficial trunk treated with surgery and perioperative high dose rate brachytherapy (PHDRB) alone or combined with external beam radiotherapy (EBRT). Rationale: Analysis of the treatment factors contributing to these complications can potentially minimize their occurrence and severity. Patients: A total of 169 patients enrolled in two parallel prospective studies were included in this analysis. Previously Unirradiated cases (Group 1; n  = 139) were treated with surgical resection, 16–24 Gy of PHDRB and 45 Gy of EBRT. Adjuvant chemotherapy was given to selected patients with high-grade tumors. Previously irradiated cases (Group 2; n  = 30) were treated with surgical resection and 32–40 Gy of PHDRB without further EBRT. Methods: Patient factors, tumor factors, surgical factors, PHDRB factors and EBRT factors were analyzed using Cox univariate and multivariate analysis. Results: In Previously Unirradiated cases, WHC, ORN and ND occurred in 38.8%, 5.0% and 19.4%. Multivariate analysis indicated that WHC increased with CTV size ( p  = 0.02) and CTV2cm3 Physical dose ( p  = 0.02). ORN increased with Bone2cm3 EQD2 ≥ 67 Gy ( p  = 0.01) and ND was more frequent in patients with TV100  DVH-based dose (tissue volume encompassed by the 100% isodose) ≥ 84 Gy ( p  < 0.01). In Previously Irradiated cases, WHC, ORN and ND occurred in 63.3%, 3.3% and 23.3%. Multivariate analysis showed that WHC was more frequent in patients with Skin2cm3  Lifetime EQD2 ≥ 84 Gy ( p  = 0.01) and ND was more frequent after CTVD90 Physical Doses ≥ 40 Gy ( p  < 0.01). Conclusions: WHC in Previously Unirradiated patients can be minimized by using a more conservative CTV definition together with a meticulous implant technique and planning aimed to minimize hyperdose CTV2cm3 areas. In Previously Irradiated patients WHC may be mimimized considering Lifetime EQD2 Skin2cm3 doses. ORN can be reduced by using the Bone2cm3 EQD2 constraint. ND occurs more frequently in patients with large tumors receiving high treated volume doses, but no specific constraints can be recommended due to the lack of peripheral nerve definition during brachytherapy planning.